DESIGN OF DRAWING BOOK AS A VEGETATION INTRODUCTION MEDIA FOR CHILDREN - Widyastuti, Herlina (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2020)
Children have an important role as the nation's next generation who will take part in protecting and building environmental sustainability. Expected later this knowledge grew into a good habit of his mature later. Through the science of visual communication design, the authors provide an alternative learning tool for children in the field of plant science to develop the children's understanding of the plant through an illustrated book with the title